Trimble m3 1``and south NTS-362R total station angle measurement accuracy analysis = Analiza dokładności pomiarów kątowych tachimetrami elektronicznymi Trimble M3 1``oraz South NTS-362R - Oleniacz, Grzegorz; Skrzypczak, Izabela; Świętoń, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this study was to obtain information about the actual precision of angle measurements with two instruments (Trimble M3 1``and South NTS-362R), realizable in given measurement conditions. This object is achieved by using a simplified method of testing instruments contained in the PN-ISO 17123-3 standard.
Keywords: ISO standard; angle measurement; accuracy analysis; norma ISO; pomiar kątów; analiza dostępności